UJI AKTIVITAS LARVASIDA EKSTRAK TERPURIFIKASI DAGING BUAH MIMBA (Azadirachta indica A. Juss.) ASAL PULAU LOMBOK TERHADAP Aedes aegypti - Selpida Handayani; Aktsar Roskiana A.; Umi K. R. Karim (Fakultas Farmasi UMI, 2013)
Neem (Azadirachta indica A.Juss.) Is a plant that has medicinal benefits as malaria, antitukak stomach and is also can used as natural insecticides, fungicides, larvicides and antifertility. This Research aims to know the mortality rate of larvae of Aedes aegypti with LC50 values indicated. Neem fruit plucked from a tree lombok island.neem. Extracts obtained by maceration solvent with the masceration methanol. Retrieved rendamen extract as much as 25,17%, then purified with n-hexane solvent. Larvasida test used 180 larvae of Aedes aegypti first instar III. Test solutions were made in 4 concentration, positive control using powder Abate® (Themephos), and a negative control. Observations were made after 24 hours of treatment . Aedes aegypti larval mortality analyzed with probid analysis to know LC50 and obtained phytochemical components contained in the methanol extracts were saponins and tannins. LC50 obtained from the methanol extract of neem fruit flesh is 1817,18 ± 1,075 µg/ml. This shows the methanol extract of neem fruit flesh (Azadirachta indica A.Juss.) Does not have the effect toxicity against larvae of Aedes aegypti indicated by LC50 > 1000 ppm. Keywords: Flesh neem, Azadirachta indica A. Juss., Aedes aegypti, LC50.